Development and Validation of Liquid Chromatography Method for Simultaneous Estimation of Metformin, Pioglitazone, and Glimepiride in Bulk and Pharmaceutical Dosage Form (Asian Journal of Pharmaceutics (AJP), 2025)
A simple reverse-phase high-performance liquid chromatography (RP-HPLC) method wasdeveloped and validated for simultaneous determination of Metformin hydrochloride, Pioglitazone, andGlimepiride in their pharmaceutical dosage form. The validated technique proved to be suitable for routine QAapplications.Method: The chromatographic separation was achieved using Agilent C18 column (250 mm × 4.6) 5 μm as astationary phase with mobile phase composition of Methanol and Tris buffer (pH 8) in ratio of 65:35 v/v. Themobile phase was then sonicated for 10 min and then filtered through 0.45 μm membrane. The flow rate was 1mL/min isocratic, column temperature 40°C, and ultraviolet detection at λ 227 nm.Conclusion: The retention times for metformin, pioglitazone, and glimepiride were found to be 1.227 min, 3.843min, and 7.353 min, respectively. The RP-HPLC technique was validated using the International Council forHarmonisation (ICH) guidelines. Recovery, precision, accuracy, selectivity, and robustness of the method wereevaluated according to the ICH guidelines. This method is simple, rapid, convenient, and a perfect choice for thedetermination of metformin, pioglitazone, and glimepiride from bulk and pharmaceutical formulations.